2020
DOI: 10.20944/preprints202010.0256.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sleep Health Promotion in the Workplace

Abstract: A workplace sleep health promotion program was implemented in an Italian police unit from 2016 to 2017. Of the 242 police officers in the unit, 218 (90%) agreed to take part in the program. A crossover trial was made in which the police officers were divided into two groups that performed sleep health promotion activities in the first and second year, respectively. The first group of officers showed significant sleep improvements at the end of the first year, while the second group had similar or worse paramet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“… 18 , 19 The probability of severe COVID‐19 is very high among shift workers, whose circadian rhythms are disrupted. 20 , 21 Sleep is of crucial importance for healthcare workers, even during normal times, 19 , 22 , 23 , 24 , 25 but increasing workloads and psychological pressure during the pandemic have led to significant fatigue among such professionals. Fear of infecting families and stigmatisation of healthcare workers have resulted in a lack of social support.…”
Section: Introductionmentioning
confidence: 99%
“… 18 , 19 The probability of severe COVID‐19 is very high among shift workers, whose circadian rhythms are disrupted. 20 , 21 Sleep is of crucial importance for healthcare workers, even during normal times, 19 , 22 , 23 , 24 , 25 but increasing workloads and psychological pressure during the pandemic have led to significant fatigue among such professionals. Fear of infecting families and stigmatisation of healthcare workers have resulted in a lack of social support.…”
Section: Introductionmentioning
confidence: 99%
“…The present research included some individuals with ongoing psychiatric treatment, which may also affect sleep quality. Previous studies suggested that sleep disturbance endangers the health and safety of workers, and insomnia is the most important predictor of work accidents [ 42 44 ]. Occupational stress and violence also affect sleep disturbance of workers [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, at the environmental level – making time for breaks (role of food and rest) and providing adequate facilities for storing and preparing food. Roundtable participants agreed that health and wellbeing initiatives in workplaces should encompass the interlinked pillars of health – sleep (Garbarino et al, 2020), activity and stress management (Limm et al, 2011) as well as diet. When considering dietary changes, sleep and stress have been shown to impact food choices (Al Khatib et al, 2018; Clark et al, 2016) strengthening the argument for complex interventions that target a range of health behaviours.…”
Section: What Does Workplace Nutritional Health and Wellbeing Mean?mentioning
confidence: 99%